Electrochemical Motion Tracking of Microorganisms Using a Large‐Scale‐Integration‐Based Amperometric Device. (4th May 2017) - Ino, Kosuke; Kanno, Yusuke; Inoue, Kumi Y.; Suda, Atsushi; Kunikata, Ryota; Matsudaira, Masahki; Shiku, Hitoshi; Matsue, Tomokazu
Abstract: Motion tracking of microorganisms is useful to investigate the effects of chemical or physical stimulation on their biological functions. Herein, we describe a novel electrochemical imaging method for motion tracking of microorganisms using a large‐scale integration (LSI)‐based amperometric device. The device consists of 400 electrochemical sensors with a pitch of 250 μm. A convection flow caused by the motion of microorganisms supplies redox species to the sensors and increases their electrochemical responses. Thus, the flow is converted to electrochemical signals, enabling the electrochemical motion tracking of the microorganisms. As a proof of concept, capillary vibration was monitored. Finally, the method was applied to monitoring the motion of Daphnia magna . The motions of these microorganisms were clearly tracked based on the electrochemical oxidation of [Fe(CN)6 ] 4− and reduction of O2 .